Tinjauan Epistemologi Terhadap Pancasila Sebagai Dasar Negara Republik Indonesia - Surajiyo, Surajiyo (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
Pancasila was not born as an epistemological system. Pancasila was born as the basis of the State, is an ideology and contains a view of life. This happened in 1945. Epistemology was born long before the birth of Pancasila. Epistemology was born from the efforts of the sophists in Ancient Greece to modern times, which placed the study of epistemology as closely related to the structure of knowledge. The epistemological basis of Pancasila is essentially inseparable from is ontological basis. Pancasila as an ideology is rooted in its basic values, namely the philosophy of Pancasila. Therefore, the basic epistemology of Pancasila cannot be separated from its basic concept of human nature. If humans are the ontological basis of Pancasila, then it has implications for the epistemological building, namely the epistemological building placed in the building of human philosophy. The research was carried out in a literal way, with a literature review of selected books and journals or scientific magazines containing descriptions of philosophy, ideology, Pancasila philosophy, epistemology, philosophy of science, and history of philosophy. The data needed is qualitative data that is processed by the reflective method, equipped with the ’verstehen’ method. The issue of epistemology in relation to Pancasila is intended to find sources of knowledge, the truth of Pancasila and the composition of Pancasila as a system of knowledge. The source of knowledge from Pancasila is seen from the flow of knowledge, namely empiricism and rationalism.